Evaluation of Novel Approaches to Software Engineering 5th International Conference, ENASE 2010, Athens, Greece, July 22-24, 2010, Revised Selected Papers - Maciaszek, Leszek A.; Loucopoulos, Pericles; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book contains a collection of thoroughly refereed papers presented at the 5th International Conference on Evaluation of Novel Approaches to Software Engineering, ENASE 2010, held in Athens, Greece, in July 2010. The 19 revised and extended full papers were carefully selected from 70 submissions. They cover a wide range of topics, such as quality and metrics; service and Web engineering; process engineering; patterns, reuse and open source; process improvement; aspect-oriented engineering; and requirements engineering.
Keywords: Computer science; Computer Communication Networks; Software engineering; Logic design; Information Systems; Computer Science; Software Engineering; Logics and Meanings of Programs; Computer Communication Networks; Programming Languages, Compilers, Interpreters; Information Systems Applications (incl. Internet).; Management of Computing and Information Systems